Nocturnal temperature-controlled laminar airflow device for adults with severe allergic asthma: the LASER RCT - Kapoor, M; Storrar, W; Balls, L; Brown, T; Mansur, A; Hedley, E; Jones, T; Roberts, C; Shirkey, B; Dutton, S; Luengo-Fernandez, R; Little, M; et al. (NIHR Journals Library, 2019)
Background Severe asthma exacerbations are costly to patients and the NHS, and occur frequently in severely allergic patients. Objective To ascertain whether or not nocturnal temperature-controlled laminar airflow (TLA) device usage over 12 months can reduce severe exacerbations and improve asthma control and quality of life compared with a placebo device, while being cost-effective and acceptable to adults with severe allergic asthma. Trial Design A pragmatic, multicentre, randomised, double-blind, placebo-controlled, parallel-group, superiority trial with qualitative interviews. The trial included an internal pilot with qualitative focus groups. Setting Fourteen hospitals in the UK that manage patients with severe asthma. Participants Adults (16–75 years) with severe, poorly controlled, exacerbation-prone asthma despite high-intensity treatment, and who are sensitised to a perennial indoor aeroallergen. Intervention Nocturnal, home-based TLA treatment using an Airsonett® (Airsonett AB, Ängelholm, Sweden) device. The comparator was a placebo device that was identical to the active device except that it did not deliver the laminar airflow. Participants were allocated 1 : 1 to TLA therapy or placebo, minimised by site, origin of case, baseline severe exacerbation frequency, maintenance oral corticosteroid use and pre-bronchodilator forced expiratory volume in 1 second. Main outcome measures Primary outcome – frequency of severe asthma exacerbations occurring within the 12-month follow-up period, defined as worsening of asthma requiring systemic corticosteroids [≥ 30 mg of prednisolone or equivalent daily (or ≥ 50% increase in dose if on maintenance dose of ≥ 30 mg of prednisolone)] for ≥ 3 days. Secondary outcomes – changes in asthma control, lung function, asthma-specific and global quality of life for participants, adherence to the intervention, device acceptability, health-care resource use and cost-effectiveness. Results Between May 2014 and January 2016, 489 patients consented to participate in the trial, of whom 249 failed screening and 240 were randomised (n = 119 in the treatment group and n = 121 in the placebo group); all were analysed. In total, 202 participants (84%) reported use of the device for 9–12 months. Qualitative analyses showed high levels of acceptability. The mean [standard deviation (SD)] rate of severe exacerbations did not differ between groups [active 1.39 (1.57), placebo 1.48 (2.03); risk ratio 0.92, 95% CI 0.66 to 1.27; p = 0.616]. There were no significant differences in secondary outcomes for lung function, except for a reduction in mean daily peak expiratory flow [mean (SD) difference 14.7 l/minute (7.35 l/minute), 95% CI 0.32 to 29.1 l/minute; p = 0.045) for those in the active device group. There were no differences in asthma control or airway inflammation and no serious harms related to the device. No significant difference between the groups in quality-adjusted life-years gained over 1 year was observed. In addition, there was no difference in generic or disease-specific health-related quality of life overall, although statistically significant higher quality of life at month 6 was observed. Increases in quality of life were not sufficient to offset the annual costs associated with use of the TLA device. Limitations Missing outcome data could have resulted in an underestimation of exacerbations and rendered the study inconclusive. Conclusions Within the limits of the data, no consistent benefits of the active device were demonstrated, and the differences observed were not sufficient to make the device cost-effective. The types of patients who may benefit from the TLA device, and the reasons for large reductions in exacerbation frequency in severe asthma trials, which also incorporate other methods of recording exacerbations, need to be explored.